Penilaian Sistem Pelayanan Infrastruktur Air Minum Program Pamsimas (Studi Kasus Kabupaten Cilacap ) - Setyoadi, Nino Heri (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
Provision of drinking water infrastructure in Pamsimas program must consider the type of service for which the condition of community. Not all service system can be accepted and adapted by the community. Reality showed existence of conflicts over water and changes in the structure and system of social relationships due to lack of appropriate services. This study is aimed to establish a system of performance indicators in water services and measure the performance of water service on Pamsimas program. This study used multi-criteria evaluation with maximum standardization and interval standardization assessment techniques to measured the performance of water service. The indicators used in assessing the performance include coverage of services, reach of the poor, smoothness of user fees, contribution fees, percentage of stop defecation and ratio of incidence of water borne disease. Assessment results showed that these indicators are able to describe and measure the performance of water services on Pamsimas program. In addition, the household connection service system is evaluated as the most appropriate system to the conditions of community in Cilacap regency.